Propuesta de mejora para la reducción de costos de producción en proyectos de pilotes pre - excavados en la empresa PSV Constructores S.A. - Peña Camerano, Natalia Alejandra (2020)
Globalization and human being tendency to create a connection between nature and the infrastructure necessary for industrial activity constitute the most effective combination when generating improvements in the foundations of the great buildings and bridges of the world. The taller a building is or the greater the distance between the supports of a bridge, the greater the demands are of the foundations that support them. Deep foundations carried out with drilled piles have become the most practical and economical solution when satisfying resistance requirements dependent on superstructures. These piles vary in length and diameter according to the demands of the project, and in order for it to be executed, drilling accessories and heavy machinery are used, that allow in synthesis, to make a hole in the ground, similar to the action of drilling a hole in the wall of a house with an electric hand drill. Drilling tools use consumables known as bits, which constitute the fusible element in the production train, since they have a relatively low cost compared to the cost of the machine itself, and are manufactured and used exclusively to wear out, fracture or fail during the drilling process of the piles. A priori, there is currently no way to predict the number of bits that will be used in the execution of the piles of an “x” project. The above would have no interest if the bits are made in the country of “x” project, however, because they are brought in from China or Germany by sea, with a delivery time ranging from 45 to 60 days, there is a lot of interest on behalf of the companies. When the estimate of the number of bits is not correct and the project runs out of these consumables without having finished all the drilled piles, the logistics supply chain has to intervene to accelerate the acquisition by air, which also translates to a dead time of production from 7 to 10 days, accompanied by the increase in general expenses, acquisition of a product at a higher cost and the most shocking for the company, penalties for stoppages or being out of contractual term. Under this context, the question that arises is the following: Is it possible to reduce production costs in a drilling rigs project with certain geometric characteristics that guarantees the profitability of the project and customer satisfaction to avoid negative impacts?